Target Financial Reporting Quality and M&A Deals that Go Bust* - Skaife, Hollis A.; Wangerin, Daniel D. (Contemporary Accounting Research, 2013)
This study investigates the role of financial reporting quality in merger and acquisition (M&A) deals that are ultimately terminated (i.e., go bust). If a target is a U.S. publicly traded company, an acquirer’s initial assessment of the potential benefits associated with the acquisition of the company is based on publicly available information. Generally, the acquirer obtains limited private information from the target prior to announcing the deal, but engages in transactional due diligence after signing the acquisition agreement to affirm that the financial reporting warranties made by the target are accurate. We construct a low‐quality financial reporting score based on measures prior research identifies as being associated with less reliable, less relevant, and less precise financial reporting. We find that acquirers offer higher premiums for targets with low‐quality financial reporting. However, we also find that low‐quality financial reporting increases the likelihood of deal renegotiation, and contributes to the probability of deals going bust. We document that failed targets are more likely to restate their financial statements after the announcement of the deal, supporting our conjecture that low‐quality financial reporting contributes to deals being terminated. Our research develops a new measure of low‐quality financial reporting, documents that the measure is related to M&A deal outcomes and financial restatements, and provides insights into the consequences of M&A transactional due diligence.